Drawing Stages in Children Aged 4-5 Years at Paud Aisyiyyah Al-Huda (Pk) Kismoyoso - Larasati, Trias; Darsinah, Darsinah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: Drawing is one of the most universal forms of self-expression in early childhood. This article describes the stages of drawing development for children aged 4-6 years, starting from the stage of random scribbling to the emergence of primitive symbols that represent objects in the real world. Apart from that, this article also presents the benefits of drawing for children's development as well as tips for parents in supporting children's creativity through drawing activities. Methodology: The research that was carried out took place at the Aisyiyyah Alhuda (PK) Kismoyoso preschool, with the results of the research carried out for 1 month of observation and producing 1 different picture every week, with the hope of knowing the child's stages each week. This observation was carried out on 4 different children. with an age range of 4-5 years. Results: Apart from that, this article also presents the benefits of drawing for children's development as well as tips for parents in supporting children's creativity through drawing activities. Applications/Originality/Value: Apart from that, this article also presents the benefits of drawing for children's development as well as tips for parents in supporting children's creativity through drawing activities.